The Limb Salvage Approach for the Surgical Management of Necrotizing Soft Tissue Infection - Johnson Boey, DPM; Longbiao Yu, MD; Zeng Hui, MD; Fanbin Meng, MD; Shengxiang Wan, MD; Yingfeng Xiao, MD; Zhou Zhegang, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Necrotizing soft tissue infection (NSTI) is a complex infection known for its rapid progression of necrosis within the subcutaneous tissue and fascia. Time is of essence for the management of NSTI. In this report, we present a case of NSTI after infection of poorly managed diabetic foot ulcer in the ankle. The limb salvage approach involves sequential staged procedures. Multiple surgical debridements and “washout” were performed for source control. At the same time, the patient also received a systemic antibiotic regimen. In the second stage, a perforator free flap taken from the anterolateral thigh was used to repair the extensive soft tissue defect and reconstruct a functional foot to achieve maximal limb salvage. The kickstand technique of external fixation was used to reduce soft tissue compression and enhance the surgical offloading of the skin flap. At the 2-year follow-up, the skin integrity of the flap was well-preserved, and the patient returned to his premorbid quality of life.